Associations between weight‐related teasing and psychosomatic symptoms by weight status among school‐aged youth - T. Warkentin; M. M. Borghese; I. Janssen (Wiley, 2017)
Objective Weight‐related teasing (WT) is associated with poor mental health. This study examined whether weight status moderates the relationship between WT and psychosomatic symptoms within a representative sample of school‐aged youth. Methods Data are from the Canadian 2013/2014 Health Behaviour in School‐aged Children Survey, a nationally representative sample of youth in Grades 6-10. WT, psychosomatic symptoms and body mass index (BMI) were self‐reported. Results The final sample consisted of 20,277 youth (mean age = 14.2 years; 50.2% female). The prevalence who reported being WT at least once a week was 4.6%, 8.1% and 17.3% among youth with normal weight, overweight, and obesity, respectively (p < 0.001). There was a gradient relationship between the frequency of WT and psychosomatic symptoms (p < 0.001). By comparison to youth that were not WT, psychosomatic symptom z‐scores were significantly (p < 0.05) higher in youth that were WT one to two times in the past few months (0.47, 95% CI: 0.41-0.53), two to three times per month (0.65, 0.52-0.77), about once a week (0.82, 0.71-0.93) and several times a week (0.98, 0.84-1.12). However, the WT * BMI category interaction term was not significant (p = 0.86). Conclusions Victims of WT experienced more psychosomatic symptoms independent of BMI category; however, BMI category did not moderate the association between WT and psychosomatic symptoms.